2015
DOI: 10.1177/2156587215595152
|View full text |Cite
|
Sign up to set email alerts
|

Bougainvillea spectabilis Exhibits Antihyperglycemic and Antioxidant Activities in Experimental Diabetes

Abstract: The study investigates the effects of aqueous extract of Bougainvillea spectabilis leaves on blood glucose, glycosylated hemoglobin, lipid profile, oxidative stress, and on DNA damage, if any, as well as on liver and kidney functions in streptozotocin-induced diabetes in Wistar rats. Daily administration of the aqueous extract of B spectabilis leaves for 28 days resulted in significant reduction in hyperglycemia and hyperlipidemia as evident from restoration of relevant biochemical markers following extract ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
3
24
0
1
Order By: Relevance
“…Increased protein catabolism with inflow of amino acids to liver occurs in DM, which feed gluconeogenesis and accelerate ureagenesis, resulting in hypo-proteinemia and hypo-albuminemia [49]. Hyperglycemia causes elevation in the levels of serum creatinine and reduction in serum total protein and albumin, which are considered as significant markers of renal dysfunction [50][51][52][53]. In the present work, EMC treatment demonstrated marked hike in the serum total protein and albumin level, whereas, fall in the levels of serum creatinine.…”
Section: Nephroprotectivementioning
confidence: 99%
“…Increased protein catabolism with inflow of amino acids to liver occurs in DM, which feed gluconeogenesis and accelerate ureagenesis, resulting in hypo-proteinemia and hypo-albuminemia [49]. Hyperglycemia causes elevation in the levels of serum creatinine and reduction in serum total protein and albumin, which are considered as significant markers of renal dysfunction [50][51][52][53]. In the present work, EMC treatment demonstrated marked hike in the serum total protein and albumin level, whereas, fall in the levels of serum creatinine.…”
Section: Nephroprotectivementioning
confidence: 99%
“…The antidiabetic effect was also seen with oral administration of aqueous extract from apical leaves of B . spectabilis [ 61 , 76 ]. Studies carried out on the steam bark extract of B. spectabilis orally administered in albino rats showed significant hypoglycaemic activity [ 77 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…The use of apical leaves from B. spectabilis extracted with distilled water measured the biomarkers of oxidative stress in blood in diabetic male Wistar rats induced with streptozotocin. The results showed that diabetic rats presented a significant decrease in GSH, SOD, and catalase [ 61 ]. Another study of B. spectabilis leaves extracted with acetone, chloroform, methanol, petroleum ether, and water also showed the high antioxidant activity [ 46 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…In Brazil, among the species of ornamental plants, Bougainvillea (Bougainvillea spectabilis Willd), belonging to the Nyctaginaceae family, also known as três-marias, ceboleiro, santa-rita, espinho-de-santa rita, is a popular ornamental plant grown in many parts of the world in tropical and subtropical gardens for its colorful bracts of red, pink, yellow and white flowers [3] [4]. In addition, its leaf extract has shown medicinal properties of anti-inflammatory [5] and hypoglycemic activity in diabetic rats [6].…”
Section: Introductionmentioning
confidence: 99%